Знатоки души человеческой: Фeдор Достоевский и Людмила Петрушевская - Lekeš, Patrik (Studia Rossica Posnaniensia, 2024)
The article deals with the works of Fyodor Dostoyevsky and Lyudmila Petrushevskaya from the point of view of two disciplines – psychology (addictology), and literary criticism. The paper explores the authors’ description of the symptoms of addiction, which manifests itself both in the consciousness, subconsciousness and behavior of literary heroes, as well as in their relationships, and the studies are reported by specific excerpts from the literary works. Based on the primary analysis of the text, it can be argued that Dostoyevsky already in the 19th century, in his works, described symptoms that were defined by psychology as a science only in the 20th century. Petrushevskaya often enters into an intertextual dialogue with Dostoevsky, describing gloomy heroes and hopeless life. The study analyzes specific symptoms and their application based on Dostoyevsky’s Netochka Nezvanova (1849) and Petrushevskaya’s The Glitch (1999). The purpose of the work is to draw attention to writers as psychologists, and to the skill of their artistic and psychological depiction of the external symptoms of various mental disorders through their literary heroes. This goal is achieved: 1) by identifying specific symptoms of mental disorders (addiction) of the characters; 2) a comparative analysis of scientific psychological material and literary text; 3) by comparing the artistic depiction of specific symptoms of characters in the texts of certain authors.